Ketimpangan Upah dalam Industri Garmen Global: Implikasi Human Security bagi Buruh di Negara Berkembang - A. Azizah Gathfani Batari (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
The global garment industry is one of the sectors most clearly reflecting the dynamics of economic globalization and the formation of global supply chains. This study aims to analyze wage inequality in the global garment industry and its implications for the human security of workers in developing countries, with a focus on Indonesia. Using a qualitative approach through library research, this study examines secondary data from scientific journals, international organization reports, government documents, and other credible sources. The findings show that wage inequality in the garment industry is not merely an economic issue but is deeply rooted in the structure of global production chains that place developing countries in a subordinate position. Multinational companies retain high-value activities such as design and branding in developed countries while relocating labor-intensive production to developing countries offering lower wage costs. This wage inequality has broad implications for multiple dimensions of human security, including economic security, health security, personal security, and community security of garment workers. Structural solutions involving governments, international organizations, multinational companies, trade unions, and civil society are needed to address this issue comprehensively. Keywords: Wage Inequality, Global Garment Industry, Human Security, Developing Countries, Global Supply Chain.